Application of bacterial spores coated by a green inorganic cementitious material for the self-healing of concrete cracks. (October 2020) - Wu, Mingyue; Hu, Xiangming; Zhang, Qian; Cheng, Weimin; Xue, Di; Zhao, Yanyun
Abstract: The Bio-based self-healing concrete requires a healing agent with excellent properties. This study used carbide slag, fly ash, and desulfurized gypsum to prepare a green inorganic cementitious material, and further developed a biocapsule by coating bacterial spores with the prepared cementitious material. Specifically, at first, the properties of the biocapsule were analyzed and the effect of its dosage on of cement mortar properties was evaluated. Then, mineralization activity was employed to characterize the ability of bacterial spores in the biocapsule to achieve mineralization. Finally, crack-healing efficiency and water permeability were evaluated to study the effectiveness of the biocapsule in crack self-healing. As per the results, addition of biocapsules at a dosage of 5% of the cement mass led to full healing of 150–550 μm width cracks. After healing, the permeability of specimens containing the biocapsule declined by about two orders of magnitude as compared with reference specimens (R). Highlights: Green cementitious materials coated with bacterial spores for self-healing of concrete cracks. The biocapsules have good compatibility with concrete and can improve the strength of concrete. Self-healing of concrete cracks has the potential to improve the durability of concrete.